2012
DOI: 10.1063/1.3685584
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative interpretation of the very fast electronic relaxation of most Ln3+ ions in dissolved complexes

Abstract: In a reference frame rigidly bound to the complex, we consider two Hamiltonians possibly at the origin of the very fast electronic relaxation of the paramagnetic lanthanide Ln(3+) ions (Ln = Ce to Nd, Tb to Yb), namely the mean (static) ligand-field Hamiltonian and the transient ligand-field Hamiltonian. In the laboratory frame, the bombardment of the complex by solvent molecules causes its Brownian rotation and its vibration-distorsion dynamics governing the fluctuations of the static and transient terms, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Thus, the lower electric charge and weaker metal–donor electrostatic interactions of Mn 2+ complexes compared to those for Gd 3+ analogues is likely responsible for the shorter τ c values of the former. Recent measurements of the longitudinal relaxation rates of ligand nuclei around complexed Ln 3+ ions and previous theoretical discussion about these systems indicated that the vibrational correlation time gives a lower bound to the longitudinal electronic relaxation time values, which should not be significantly less than the inverse of the solvent collision frequency (∼0.1 ps). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the lower electric charge and weaker metal–donor electrostatic interactions of Mn 2+ complexes compared to those for Gd 3+ analogues is likely responsible for the shorter τ c values of the former. Recent measurements of the longitudinal relaxation rates of ligand nuclei around complexed Ln 3+ ions and previous theoretical discussion about these systems indicated that the vibrational correlation time gives a lower bound to the longitudinal electronic relaxation time values, which should not be significantly less than the inverse of the solvent collision frequency (∼0.1 ps). , …”
Section: Resultsmentioning
confidence: 99%
“…Recent measurements of the longitudinal relaxation rates of ligand nuclei around complexed Ln 3+ ions and previous theoretical discussion about these systems indicated that the vibrational correlation time gives a lower bound to the longitudinal electronic relaxation time values, which should not be significantly less than the inverse of the solvent collision frequency (∼0.1 ps). 75,76 The transient ZFS (Δ T ) was estimated from the spread of the Δ values along the trajectories obtained with ADMP simulations (Figure 6). The ZFS energy calculated for [Mn(MeNO2A)(H 2 O)]•2H 2 O shows important fluctuations along the trajectory of our MD simulations, whereas it fluctuates to a lesser extent for [Mn(EDTA)(H 2 O)] 2− •2H 2 O.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The correlation time for dipolar relaxation is governed by the electron spin relaxation time T e which is, for lanthanides (except Gd 3+ ), much shorter than τ m and τ R , the rotational correlation time for the reorientation of the electron spin–proton vector …”
Section: Theory and Data Treatmentmentioning
confidence: 99%
“…The correlation time for dipolar relaxation is governed by the electron spin relaxation time T e which is, for lanthanides (except Gd 3+ ), much shorter than τ m and τ R , the rotational correlation time for the reorientation of the electron spin− proton vector. 25 The outer sphere relaxivity refers to relaxation enhancement due to solvent molecules in the second coordination sphere and bulk solvent and is given as the sum of the dipolar and Curie relaxations. The dipole−dipole relaxation is described by eq 7, developed by Freed 26,27 and Ayant.…”
mentioning
confidence: 99%
“…, although temperature‐dependent changes in viscosity of biological matrixes, and thus rotational correlation times, are nontrivial. Values of T 1e for the considered lanthanides are in the order of 10 −13 s, just above the solvent‐complex collision boundary . Because τ r >> T 1e for the studied ions, the first term of Eq.…”
Section: Theorymentioning
confidence: 98%